1998
DOI: 10.1056/nejm199808273390902
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Compared with Intravenous Epoetin in Patients Receiving Hemodialysis

Abstract: In patients receiving hemodialysis, subcutaneous administration of epoetin can maintain the hematocrit in a desired target range, with an average weekly dose of epoetin that is lower than with intravenous administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
2
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(85 citation statements)
references
References 23 publications
5
75
2
1
Order By: Relevance
“…In Europe and the USA, many clinical studies comparing intravenous and subcutaneous injections revealed that subcutaneous injection of rHuEPO is more advantageous than intravenous injection in terms of the improvement in anemia and its long-lasting effect, as well as costeffectiveness [64][65][66][67][68][69][70][71][72][73][74][75][76][77]. In the conventional European and US guidelines on therapy for renal anemia [78,79], subcutaneous injection was also recommended for HD patients.…”
Section: (2)target Hb Levels To Be Maintained In Pd Patientsmentioning
confidence: 99%
“…In Europe and the USA, many clinical studies comparing intravenous and subcutaneous injections revealed that subcutaneous injection of rHuEPO is more advantageous than intravenous injection in terms of the improvement in anemia and its long-lasting effect, as well as costeffectiveness [64][65][66][67][68][69][70][71][72][73][74][75][76][77]. In the conventional European and US guidelines on therapy for renal anemia [78,79], subcutaneous injection was also recommended for HD patients.…”
Section: (2)target Hb Levels To Be Maintained In Pd Patientsmentioning
confidence: 99%
“…28 Therapy with erythropoietin is useful in diseases complicated by anemia with low or inadequate erythropoietin levels, such as end-stage renal disease, multiple myeloma, rheumatoid arthritis, and prematurity. 4,5,[7][8][9][10] Therapeutic administration of erythropoietin can improve hemoglobin levels and anemic symptoms in many patients with these disorders. Our results suggest that patients with cirrhosis who have inappropriately low serum erythropoietin levels may also benefit from treatment with exogenous erythropoietin.…”
Section: Discussionmentioning
confidence: 99%
“…The prolonged half-life following subcutaneous administration of epoetin beta suggested the possibility of increasing the interval between injections when using this route of administration, as confirmed by rHuEPO levels remaining within the target range for most of the period between injections even with once-weekly subcutaneous dosing (Besarab et al 1992). In addition, dose requirements to maintain target hemoglobin levels are significantly lower when epoetin beta is administered subcutaneously compared with intravenously (Besarab et al 1992;Kaufman et al 1998). For this reason, current treatment guidelines (Locatelli et al 2004a) recommend the subcutaneous route of administration of epoetin beta in order to minimize treatment costs.…”
Section: Epoetin Beta and Renal Anemia Clinical Pharmacologymentioning
confidence: 99%
“…Finally, different studies reported that once-weekly subcutaneous epoetin beta is as well tolerated as two-or three-times-weekly regimens (Weiss et al 2000;Locatelli et al 2002). It must also be considered that the reduced dosage requirements when epoetin is administered subcutaneously compared with intravenously may allow substantial cost savings, without compromising effectiveness or safety of therapy (Kaufman et al 1998;Besarab et al 2002;Hynes et al 2002).…”
Section: Safety and Tolerabilitymentioning
confidence: 99%